The real interest rate gap: Measurement and application - Anders Møller Christensen (Danmarks Nationalbank, 2002)
For empirical purposes it is suggested to approximate the real interest rate gap by a simple transformation of the difference between two nominal interest rates, the central bank's policy rate and the long-term interest rate. The latter contains information on inflationary expectations and expected real returns from other assets. The suggested measure is used for an empirical analysis of recent monetary policy in a few countries and some new, although preliminary interpretations are obtained, in particular concerning the US and Sweden. In addition, arguments are put forward to include the measure in the analyses under the first pillar of the ECB. The measure is readily available in real time.
Keywords: 330; Kaufkraftparität; Theorie